E-Learning Applications of Animals’ Names Based on Mobile Web - Wan, Yuliyanti; Khairul Anwar Hafizd; Rakhmata, Muhammad (Jurnal Humaniora Teknologi, 2021)
E-Learning applications of animals’ names are made to meet the needs of interactive, interesting and easy to understand. It is such a learning media that is created based on the mobile web both for early childhood, elementary school, or high school. This learning media called e-learning applications of animals’ names based on mobile web that can be used as a media to recognize or memorize the animals’ names by using text (text), images (visual), and sound (audio) both in Indonesian and English. Particularly for the Junior High School, the learning media will help the students to review or memorize the animals’ names at home on their mobile phone or smartphone. On the other side, the students’ smartphones are not only use as social media or playing game, but also for learning English, especially learning the animals’ names, anytime and anywhere. Keywords: E-Learning, Applications, animals’ names.